2021
DOI: 10.1136/bmjopen-2020-044777
|View full text |Cite
|
Sign up to set email alerts
|

Young adults’ perceptions of living with atopic dermatitis in relation to the concept of self-management: a qualitative study

Abstract: ObjectivesLearning to take control of one’s health is an important part of the transition from adolescence to adulthood. This study aimed to explore young adults’ perceptions of living with atopic dermatitis (AD) in relation to the concept of self-management.DesignA qualitative study with an inductive approach was performed through semistructured interviews (n=15). The interviews were recorded, transcribed verbatim and analysed with systematic text condensation.ParticipantsYoung adults (mean age 23,4 years) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…In the US, a higher proportion of patients rated their AD as less severe than did their treating clinician ( 17 ). In a qualitative semi-structured interview study, young adults suggested that, despite their AD being a constant in their lives, most had become used to living with the condition ( 18 ). In addition, patients, despite having experience of AD since childhood, may nevertheless feel uncertainty about options for treatment of the disease.…”
mentioning
confidence: 99%
“…In the US, a higher proportion of patients rated their AD as less severe than did their treating clinician ( 17 ). In a qualitative semi-structured interview study, young adults suggested that, despite their AD being a constant in their lives, most had become used to living with the condition ( 18 ). In addition, patients, despite having experience of AD since childhood, may nevertheless feel uncertainty about options for treatment of the disease.…”
mentioning
confidence: 99%
“…Twenty-four studies addressed patients valuing education from clinicians on how to use a treatment. This included verbal communication, written instructions, and demonstrations of how to apply topical treatments (low certainty):…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies addressed patients valuing education from clinicians on how to use a treatment. This included verbal communication, written instructions, and demonstrations of how to apply topical treatments (low certainty) 12,15,16,20,21,25,27,31,32,36,37,41,43,46,48,49,56,58,61,65,67,[69][70][71][72] : "It would be good if they showed you how to apply the cream, when collecting it for the first time." 41 As a possible solution, initial supportive care and attention could be provided by nurse specialists: "A physician has limited time during a consultation…In situations like this, an additional appointment with a nurse who has time to listen to your story, who is in close contact with your physician, and could potentially discuss any important considerations, would be really appreciated."…”
Section: Strong Patient-clinician Relationship and Improved Treatment...mentioning
confidence: 99%
“…However, the difference was small and might not be considered clinically relevant ( 39 ). One explanation may be that young adults have grown accustomed to living with AD, as shown in a qualitative study from our group ( 13 ) and a qualitative study from England, including young people ( 40 ).…”
Section: Discussionmentioning
confidence: 96%
“…Most patients with AD are treated in primary care ( 11 , 12 ). Data from our population-based cohort have shown that young adults with AD since childhood had never felt completely asymptomatic and had experienced difficulties in getting help from healthcare ( 13 ). A European cross-sectional register study in adults showed that patients with uncontrolled AD had a greater disease burden than those with controlled AD ( 14 ).…”
mentioning
confidence: 99%